Towards Bio-Crude Refinery Integration: Hydrodeoxygenation and Co-Hydroprocessing with Light Cycle Oil - Athanasios Dimitriadis; Stella Bezergianni (Energies)
Hydrothermal liquefaction of solid waste has been gaining more and more attention over the last few years. However, the properties of the HTL product, i.e., biocrude, are limiting its direct utilization. As a result, HTL biocrude upgrading is essential to improve its quality. The main objective of the current research is to study the hydrotreatment stabilization of HTL biocrude, produced from spent coffee grounds, utilizing commercial hydrotreated catalysts, and also to investigate the integration of the stabilized biocrude into a light cycle oil (LCO) hydrotreatment plant for coprocessing to target hybrid fuel production. The results have shown that hydrotreatment is a very promising technology that can successfully remove the oxygen content from raw biocrude by hydrodeoxygenation, decarbonylation and decarboxylation reactions, leading to a stabilized product. The stabilized product can be easily blended with the LCO stream of a typical refinery, leading to the production of jet and diesel boiling range hydrocarbons, favoring at the same time the hydrogen consumption of the process. The findings of this manuscript set the basis for future research targeting the production of renewable advanced biofuels from HTL biocrude from municipal waste.